Are There Economic Influences on Choice for Sterilization by Minority Women in an Inner-City Hospital? [187]. (May 2015) - Hamaoui, Abraham; Upadhyay, Ruchi; Contin Mendoza, Oscarina Altagracia; Henderson, Cassandra E.; Mercado, Ray Anthony; Santiago, Crystal Marie
Abstract : INTRODUCTION: Female sterilization is one of the most widely used methods of family planning by women in general and minorities in particular. Few articles have looked at the effect of economic changes on the decision to undergo sterilization by minority women. METHODS: This is a retrospective study of women admitted to our service from January 1, 2007, to December 31, 2012, who received permanent sterilization in the postpartum period. Rates of tubal sterilization were compared with unemployment rates obtained from the Bureau of Labor Statistics. RESULTS: Approximately 2 years into the recession, deliveries continued to rise but dropped off as the recession deepened before its peak in 2010 and continued to do so for another year before rising again as the economy recovered employment. However, the rate of tubal ligations fell early on, declining steadily from 7.75% in 2007 to 2.81% in 2010. This mirrored inversely the steady rise of unemployment of 4.6–9.7% in those years. From then on, as unemployment improved, the number of tubal ligations increased (7.37% in 2011, and 5.60% in 2012). CONCLUSION AND IMPLICATION: Although it has been reported that in periods of economic declines fertility rates trend down, the findings of this study that permanent sterilizations are reduced in economic depression is interesting. We would speculate that in a population with a limited number of wage earners, the loss of wages is significant enough to postpone the choice for sterilizations. This study is limited to one institution, and further work should expand these findings.